Servant Leadership’s Impact on Green Behavior: Exploring Psychological Empowerment and Autonomous Motivation for the Environment in the Energy Sector - Harina, Rahmah Nabila; Rachmawati, Riani (Universitas Airlangga, 2024)
Objective: This study aims to understand the influence of servant leadership on employees’ voluntary green behavior and green innovative work behavior, with psychological empowerment and autonomous motivation for the environment playing a role as sequential mediators in the energy sector. Design/Method/Approach: Data was gathered through an online questionnaire sent to potential participants. A total of 328 eligible respondents were collected for analysis. This study utilized Covariance-Based Structural Equation Modelling (CB-SEM) to examine the connections between servant leadership, psychological empowerment, autonomous motivation for the environment, employees’ voluntary green behavior, and green innovative work behavior. Findings: A servant leader who influences employees' voluntary green behavior and green innovative work behavior must build psychological empowerment and autonomous motivation for the environment. In line with previous research, the role of mediation, psychological empowerment, and autonomous motivation for the environment simultaneously strengthen servant leaders to form environmentally friendly behavior. Originality: The novelty of this study lies in adding the variable green innovative work behavior as a dependent variable that can be influenced by servant leadership. Previous studies have not combined green innovative work behavior with psychological aspects, including psychological empowerment and autonomous motivation for the environment. This research is conducted in the energy sector, which is expected to yield diverse results depending on the influencing factors. Practical/Policy implication: Based on the findings, leaders, and management should promptly consider implementing employee development through servant leadership interventions. In the era of energy transition, these behaviors are crucial, with servant leadership, psychological empowerment, and autonomous motivation for the environment playing pivotal roles. Implementing these practices meets green bond criteria, indicating the company's commitment to environmentally friendly practices and enhances its reputation as an environmentally responsible entity, attracting stakeholders supportive of such initiatives.